2018
DOI: 10.1177/1476718x18809388
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic of care: Preschool children’s caring expressions and enactments

Abstract: Children engage in a multitude of reciprocal relationships of care within Early Childhood Care and Education settings; they act as both care-receivers and care-givers. In order to better understand the ways in which children construct care (i.e. as they receive it and provide it to others), this study investigated how 15 threeto five-year-olds expressed, enacted, and then subsequently described and explained their experiences of care in one preschool classroom in the Midwestern United States. Data were capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(42 reference statements)
1
5
0
1
Order By: Relevance
“…A recent study by Schmerse and Hepach (2021) found that both parent and teacher socialization goals, but also the social climate among peers in the classroom group, predicts young children’s concern for others and their subsequent acts of help between the ages of two and four: children who received good quality of care in both the family and daycare environments and who experienced a pleasant climate of peer interaction exhibited more prosocial behavior than children who grew up early only in the family context. These findings are consistent with those from previous studies that showed good daycare experience can promote prosociality ( Hyson and Taylor, 2011 ; Grazzani et al, 2016 ; Quigley and Hall, 2016 ; McCormick, 2018 ). In contrast, Bleiker et al (2019) highlighted that prosocial behavior of children aged 18-24 months who attended daycare did not differ from that of family-raised peers; furthermore, a study by Pingault et al (2015) showed that, at age six, children with daycare experience were more sociable but equally prosocial than others.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…A recent study by Schmerse and Hepach (2021) found that both parent and teacher socialization goals, but also the social climate among peers in the classroom group, predicts young children’s concern for others and their subsequent acts of help between the ages of two and four: children who received good quality of care in both the family and daycare environments and who experienced a pleasant climate of peer interaction exhibited more prosocial behavior than children who grew up early only in the family context. These findings are consistent with those from previous studies that showed good daycare experience can promote prosociality ( Hyson and Taylor, 2011 ; Grazzani et al, 2016 ; Quigley and Hall, 2016 ; McCormick, 2018 ). In contrast, Bleiker et al (2019) highlighted that prosocial behavior of children aged 18-24 months who attended daycare did not differ from that of family-raised peers; furthermore, a study by Pingault et al (2015) showed that, at age six, children with daycare experience were more sociable but equally prosocial than others.…”
Section: Introductionsupporting
confidence: 93%
“…Indeed, the daycare experience requires children to create new relationships outside the family very early on, and this means to engage in interactions with peers, to adapt to teachers’ expectations and demands, and to test and modify their social-emotional abilities by experience ( Hyson and Taylor, 2011 ; Grazzani et al, 2016 ). As some studies have shown, while attending daycare children are frequently exposed to prosocial behaviors and, consequently, they are prone to enact such behaviors themselves for two main reasons: one refers to social imitation processing, the other to the evidence that through the care that the young children receive, they learn to care for others ( Quigley and Hall, 2016 ; McCormick, 2018 ; Bleiker et al, 2019 ; Schmerse and Hepach, 2021 ). Furthermore, the study of Over and Carpenter (2009) evidenced that the mere condition of familiarizing children with photographs in which group situations are represented, and thus clearly affiliative and social, leads them to enact more helping behaviors than children who have been exposed to non-affiliative pictures, in which isolated individuals are represented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En Turquía, se demuestra cómo el uso del método facilita el involucramiento emocional de los niños (Akyol & Erkan, 2018). En Estados Unidos, se estudia, además, el desarrollo del compañerismo (McCormick, 2018), y en México, el desarrollo de la amistad con los niños preescolares (Fritz-Macías, 2016b, 2016a.…”
Section: El Enfoque Mosaico En El Mundounclassified